Forecasting the Contribution of Renewable Energy to the Indonesian Economy: A Vector Error Correction Model Approach - Ramadhan, Muhammad Rafenza; Aprilianti, Natasya; Fadil, Nadila Istima; Wicaksono, Ahmad Tibrizi Soni (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to evaluate the causal relationship between Renewable Energy Consumption, Non-Renewable Energy Consumption, and Economic Growth. This study uses quantitative methods and analyzes data using a Granger Causality Test, Vector Error Correction Model (VECM), Impulse Response Function (IRF), and Variance Decomposition (VDC). The study was conducted in Indonesia, with data ranging from 1993 to 2022 obtained from the World Bank database and Our World in Data. The results of the study based on the Granger test show that renewable energy has a significantly positive impact on economic growth in Indonesia. According to the VECM test, renewable energy consumption contributes to increasing economic growth as a result of construction and manufacturing sector activities in the development of renewable energy in Indonesia. The government should focus on energy availability, with an emphasis on increasing the production of renewable natural resources.